Establishing a database of Canadian feline mitotypes for forensic use. (May 2016) - Arcieri, M.; Agostinelli, G.; Gray, Z.; Spadaro, A.; Lyons, L.A.; Webb, K.M.
Highlights: Domestic cat mtDNA mitotype frequency in Canada was assessed. Canadian and United States cat populations are genetically homogenous. The cat population in Canada has a noticeably higher frequency of mitotype B6 relative to the United States and the global cat population. Forensic databases for estimating cat mitotype frequency distribution should account for special cases of local frequency variation, such as mitotype B6 in Canada, even when this variation does not make the overall population "distinct.". Abstract: Hair shed by pet animals is often found and collected as evidence from crime scenes. Due to limitations such as small amount and low quality, mitochondrial DNA (mtDNA) is often the only type of DNA that can be used for linking the hair to a potential contributor. mtDNA has lower discriminatory power than nuclear DNA because multiple, unrelated individuals within a population can have the same mtDNA sequence, or mitotype. Therefore, to determine the evidentiary value of a match between crime scene evidence and a suspected contributor, the frequency of the mitotype must be known within the regional population. While mitotype frequencies have been determined for the United States' cat population, the frequencies are unknown for the Canadian cat population. Given the countries' close proximity and similar human settlement patterns, these populations may be homogenous, meaning a single, regional database may be used for estimating cat population mitotype frequencies. Here we determined the mitotype frequencies of the Canadian cat population and compared them to the United States' cat population. The two cat populations are statistically homogenous, however mitotype B6 was found in high frequency in Canada and extremely low frequency in the United States, meaning a single database would not be appropriate for North America. Furthermore, this work calls attention to these local spikes in frequency of otherwise rare mitotypes, instances of which exist around the world and have the potential to misrepresent the evidentiary value of matches compared to a regional database.